Available screening tools for adults suffering from bipolar affective disorder in primary care: An integrative literature review. Issue 5 (18th February 2015) - Hoyle, Staci; Elliott, Lydia; Comer, Linda
Abstract Purpose To assess the efficacy of six tools utilized in primary care for the screening of bipolar affective disorder (BPAD). BPAD has historically been underdiagnosed or misdiagnosed followed by inappropriate treatment leading to detrimental relapses, suicide, and increased risks for comorbidities. Data sources An electronic search was conducted to identify articles in the following databases: MEDLINE, CINAHL, Cochrane Library, ERIC, National Guideline Clearinghouse, PsycINFO, Psychology and Behavioral Sciences collection, and PsycARTICLES. Other information was also collected from the NIH, CDC, Healthy People 2020, the Black Dog Institute, and the Center for Quality Assessment and Improvement for Mental Health. Conclusion Evidence indicates that primary care providers are often the first and sometimes sole provider, which signifies the importance of early detection and screening of BPAD in primary care. By implementing the use of appropriate screening tools and following recommended treatment and intervention guidelines, the prevention of relapse is increased, and comorbidities are more frequently diagnosed leading to an overall improved quality of life. Implications for practice Primary care practitioners play a vital role in appropriately screening for BPAD and implementing the recommended treatments to increase prevention of relapse and promote a healthier and more socially successful quality of life.